2023
DOI: 10.1126/sciadv.adh3327
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Nd 1− x Eu x NiO 2 thin films using in situ synthesis

Abstract: We report on superconductivity in Nd 1− x Eu x NiO 2 using Eu as a 4f dopant of the parent NdNiO 2 infinite-layer compound. We use an all–in situ molecular beam epitaxy reduction process to achieve the superconducting phase, providing an alternate method to the ex situ CaH 2 reduction process to induce superconductivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In the case of RP films with the initial stoichiometry of Nd 6 Ni 5 O 16 , the reduced films did not exhibit superconductivity in the Nd 6 Ni 5 O 12 phase [122], contrary to the reports for MBE-grown films synthesized via CaH 2 reduction [118]. Interestingly, infinite-layer Nd 1−x Eu x NiO 2 films synthesized in this manner were superconducting and exhibit T c values of 21 K for x = 0.25 [121], higher than any previous reports for MBE or PLD-grown films. Transport data for these films is shown in figure 4.…”
Section: Nickelates: Isoelectronic Analogue To the Cupratesmentioning
confidence: 57%
See 1 more Smart Citation
“…In the case of RP films with the initial stoichiometry of Nd 6 Ni 5 O 16 , the reduced films did not exhibit superconductivity in the Nd 6 Ni 5 O 12 phase [122], contrary to the reports for MBE-grown films synthesized via CaH 2 reduction [118]. Interestingly, infinite-layer Nd 1−x Eu x NiO 2 films synthesized in this manner were superconducting and exhibit T c values of 21 K for x = 0.25 [121], higher than any previous reports for MBE or PLD-grown films. Transport data for these films is shown in figure 4.…”
Section: Nickelates: Isoelectronic Analogue To the Cupratesmentioning
confidence: 57%
“…Recent studies have particularly focused on reduction of nickelate films without CaH 2 using metallic aluminum capping layers [121,122]. In these works, the authors grew epitaxial nickelate films followed by Al capping layers without air exposure.…”
Section: Nickelates: Isoelectronic Analogue To the Cupratesmentioning
confidence: 99%
“…The most famous examples are lithium-ion batteries, where lithium is deintercalated from the host structure, allowing for the remaining lithium ions to diffuse into the empty sites within the layer. , Moreover, oxygen deintercalation via topotactic reduction has allowed for the discovery of novel families of materials with functional electronic and magnetic applications. , , Topotactic modification reveals how small changes in structure, oxidation state, and composition can greatly affect material properties, as seen by the onset of superconductivity upon the intercalation of fluorine in Sr 2 CuO 3 . Another such example is the discovery of superconductivity in reduced nickelate thin films. , …”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in detecting hydrogen in the solid state and the ambiguity of hydrogen’s role in nickelate superconductivity motivate the need for a new reduction technique. Some progress in hydride-free reductions has been shown using metals as oxygen getters such as zirconium or aluminum , , but in bulk samples hydride-free reductions have only resulted in the formation of LaNiO 2.5 instead of the desired LaNiO 2 phase. Thin film samples reduced using aluminum have required an in situ technique that does not easily transfer to bulk samples. , Aluminum also shows significant reduction potential at low temperatures when mixed with gallium, reacting with water. , However, as these are extremely powerful reductants, such reactions are very sensitive to precise timing and particle morphology, limiting reaction control and material quality.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] In 2019, Li et al reported the observation of superconductivity in Nd1−𝑥Sr𝑥NiO2 thin films with 𝑇c around 9-15 K. [9] Shortly after that, superconductivity has been extended to other hole-doped infinite-layer nickelates with different rare-earth elements and Nd6Ni5O12 with quintuple NiO2 layers. [10][11][12][13][14][15][16][17][18][19] Under high pressures, the maximal 𝑇c of 31 K in Pr0.8Sr0.2NiO2 thin film is observed. [20] However, in bulk infinite-layer nickelates, superconductivity is still absent up to date.…”
mentioning
confidence: 96%